2002
DOI: 10.1039/b108193b
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric and electrooptic relaxation spectrometry of lipid vesicle electroporation at high fields

Abstract: Electrooptic and conductometric relaxation spectrometry of lipid unilamellar vesicles (Avanti 20) of radius a ¼ 90 nm, filled with 0.2 M NaCl electrolyte, suspended in low conductive 0.33 M sucrose and 0.2 mM NaCl solution of vesicle number density r v % 2.4 Â 10 15 L À1 and exposed to a rectangular electric field pulse (up to E ¼ 7.5 MV m À1 , pulse duration t E ¼ 10 ms) has been used to quantify the structural changes involved in membrane electroporation (ME) and rapid membrane transport, sometimes also call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
(80 reference statements)
4
43
0
Order By: Relevance
“…In the latter case, the membrane tension (the driving force for the opening) relaxes as the pore widens, and so vesicles can close due to the finite edge energy. A larger number of experiments have been devoted to characterize electroporation of vesicles [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In particular, application of mechanical stress using micropipettes combined with electric field pulses allows to point out the balance between both type of forces [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, the membrane tension (the driving force for the opening) relaxes as the pore widens, and so vesicles can close due to the finite edge energy. A larger number of experiments have been devoted to characterize electroporation of vesicles [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In particular, application of mechanical stress using micropipettes combined with electric field pulses allows to point out the balance between both type of forces [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, it has been found that resealing after electroporation of a lipid membrane takes milliseconds to seconds. 13,14 Thus, if a single particle is able to disrupt a membrane, 100% leakage can be expected if the concentration of the particles is close to one particle per vesicle or more. Conversely, if leakage below 100% is found and the particle concentration is well above one particle per vesicle, then more than one particle is needed to disrupt the vesicle membrane.…”
Section: ¹1mentioning
confidence: 99%
“…13,14 A few other experiments have been performed but mainly with small vesicles, which are hundreds of nanometres in size. 45,51,52 Poration of small vesicles induced by DC pulses has attracted stronger interest. [52][53][54][55] Because of the small size of the vesicles, direct observation of the deformation and poration is not feasible.…”
Section: Vesicle Response To DC Pulsesmentioning
confidence: 99%